ANALISIS KINERJA STRUKTUR GEDUNG BERTINGKAT DENGAN MENGGUNAKAN METODE STATIC NON-LINEAR (STUDI KASUS : GEDUNG DPRD KABUPATEN MALUKU TENGAH) - Pattiwael, Krisselto; Frans, Pieter Lourens; Hutubessy, Vector R. R. (Journal Agregate, 2024)
Central Maluku Regency is an area prone to earthquakes because it is included in one of the 5th earthquake zone areas in Indonesia, so it is very necessary to analyze the performance of structures against earthquakes. The purpose of this research is to produce the displacement value between floors in the upper structure of the Central Maluku Regency DPRD Building and obtain the performance of the upper structure of the Central Maluku Regency DPRD Building with non-linear static analysis with the help of the SAP2000 v.22 program. This research shows several conclusions.Â  The displacement value between plants due to the largest X-direction earthquake load is 21.19 mm, and the largest Y-direction displacement is 20.73 mm. Evaluation of structural performance The results of the X-direction review capacity curve show that the building is included in the IO condition, while the Y-direction review provides an overview of the behavior of the structure experiencing elastic, in-elastic conditions and then experiencing collapse shown by the curve with a decrease. In the Y direction, the building is included in the IO condition. The design concept of a strong column weak beam is fulfilled, this is because, in the structural elements of the building, the beam experiences plastic conditions earlier than the column.